Complete Responses after Hyperthermic Ablation by Ultrasound Guided High Intensity Focused Ultrasound Plus Systemic Chemotherapy for Locally Advanced Pancreatic Cancer. (23rd May 2013) - Vidal-Jove, Joan; Garcia-Bernal, Marta; Perich, Eloi; Alvarez del Castillo, Manuel
Abstract : We describe results in unresectable pancreatic tumors treated with USgHIFU hyperthermia ablation plus adjuvant chemotherapy. Materials and Methods . Thirty two cases of nonresectable pancreatic tumors were treated from March 2010 to March 2012, and all of them underwent systemic chemotherapy. Clinical responses (thermal ablation achieved) were measured by image techniques. There were 23 stage III cases and 9 stage IV cases. Complications were also analyzed. Results . Clinical responses (ablation obtained) were 82% in all cases, sustained at 8 weeks of the procedure. We obtained 8 complete responses (25%) at the end of the combined treatment, 7 from stage III patients and 1 from stage IV. Major complications included (1) severe pancreatitis with GI bleeding and (2) skin burning grade III that required plastic surgery. No deaths were registered. Median survival was 12.5 month (6 months–2.5 year). Conclusion . HIFU plus SC is a potentially effective and safe modality for the treatment of unresectable pancreatic cancer.